Social and relationship capital effect on the value of firms listed on the Johannesburg Stock Exchange ? An integrated reporting approach - Dr Felix Chirairo; Prof Mashukudu Hartley Molele (Journal of Economic and Social Development (Varaždin), 2024)
Measuring and reporting the impact of Social and Relationship Capital (SRC) on firm value has continued to evade practitioners and academics alike. Integrated Reporting (IR) was expected to usher a new era where value added by non-financial capitals could be measured. However, the IR framework fell short of providing a holistic solution as it lacked a measurement tool that could be used by IR report preparers, analysts and other users of corporate reports. SRC is one of the five non-financial capitals identified in the IR framework (IIRC, 2013, 2021). This study, focusing on SRC, offers a measurement solution through the use a regression model. Adopting the stakeholder theory lens, this study decomposed SRC into six stakeholder proxies that were used in the regression model. Customers, Lenders and Shareholders showed positive statistically significant associations to market share price while Employees demonstrated a weak relationship. Government indicated a negative relationship to the same dependant variable.